A new species of Umbilia Jousseaume, 1884 (Mollusca: Cypraeidae) from the Australian Pliocene. (3rd July 2021) - Southgate, Paul C.; Militz, Thane A.; Roberts, Mike
ABSTRACT: A new morphologically distinct species of cowry (family Cypraeidae Rafinesque, 1815) is described from the Pliocene of Flinders Island, Tasmania. Diagnostic features of Umbilia furneauxensis n. sp. include relatively small size (<60 mm), extension of apertural dentition to at least midway on the ventrum and labrum, and heavily callused margins with numerous shallow depressions forming a dimpled surface that may extend on to the base. It is the third Umbilia species to be recognised from the Australian Pliocene. ZooBank registration: http://zoobank.org/urn:lsid:zoobank.org:pub:4B6291F2-DA31-4A00-A223-268A83F480AE